Parasite Mitogen-Activated Protein Kinases as Drug Discovery Targets to Treat Human Protozoan Pathogens. (15th December 2010) - Brumlik, Michael J.; Pandeswara, Srilakshmi; Ludwig, Sara M.; Murthy, Kruthi; Curiel, Tyler J.
Abstract : Protozoan pathogens are a highly diverse group of unicellular organisms, several of which are significant human pathogens. One group of protozoan pathogens includes obligate intracellular parasites such as agents of malaria, leishmaniasis, babesiosis, and toxoplasmosis. The other group includes extracellular pathogens such as agents of giardiasis and amebiasis. An unfortunate unifying theme for most human protozoan pathogens is that highly effective treatments for them are generally lacking. We will review targeting protozoan mitogen-activated protein kinases (MAPKs) as a novel drug discovery approach towards developing better therapies, focusing on Plasmodia, Leishmania, and Toxoplasma, about which the most is known.